1983
DOI: 10.1148/radiology.146.1.6849039
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of the normal neonatal adrenal gland.

Abstract: Ninety-two consecutive neonates were prospectively evaluated with real-time ultrasound to assess the frequency of adrenal visualization. The right gland was identified in 97% of neonates and the left in 83%. Criteria for normal length and width are presented. The characteristic sonographic appearance of the neonatal adrenal is described and correlated with histologic data. Ultrasound is the examination of choice for evaluating the neonatal adrenal gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 0 publications
5
33
0
Order By: Relevance
“…The correspondent Graphics are also indicated. Ferr6, 1981; Rosenberg, 1982 andOppenheimer, 1983) suggest that the adrenal weight increase in the fetal period is due to the development of the fetal zone of the adrenal cortex. According to those authors, the adrenal weight decrease in the post-natal period corresponds to the involution of that cortical zone.…”
Section: Results and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correspondent Graphics are also indicated. Ferr6, 1981; Rosenberg, 1982 andOppenheimer, 1983) suggest that the adrenal weight increase in the fetal period is due to the development of the fetal zone of the adrenal cortex. According to those authors, the adrenal weight decrease in the post-natal period corresponds to the involution of that cortical zone.…”
Section: Results and Methodsmentioning
confidence: 99%
“…Lindgren (1967) reported the importance of precocious diagnosis of the adrenal congenital pathologies (congenital hypoplasia) for therapeutic success. Recently (Rosenberg, 1982;Oppenheimer, 1983;and Hata 1985) the real time ultrasonography made possible, since the 22nd week post-conception, the identification and measurement of the dimensions of the adrenal gland, and also the distinction between cortical and medullar /ones. This work presents the growth of the adrenal gland, in attempt to determine the normal parameters which are necessary to the identification of morphological changes suggesting congenital pathological process.…”
mentioning
confidence: 99%
“…Some authors [5,6] reported the results of investigations done to assess the utility of high-frequency real-time ultrasound to dem onstrate neonatal adrenal glands and to iden tify the sonographic appearance of the glands, as related to age. Oppenheimer et al [5] reported that ultrasound visualization of the normal neonatal adrenal gland was facil itated due to the following factors.…”
Section: Resultsmentioning
confidence: 99%
“…In particular a right adrenal gland is identified in essentially 100% of newborns. 1 The absence of identifiable adrenal glands suggests either deficient adrenocorticotropin hormone or adrenal hypoplasia congenita (AHC). The latter is a rare condition.…”
Section: Denouement and Discussionmentioning
confidence: 99%